Kshetrikaran –A Multipronged Ayurvedic Strategy To Enhance FertilitKshetrikaran –A Multipronged Ayurvedic Strategy To Enhance Fertility Outcomes In Women Wy Outcomes In Women With Uterine Cavitary Defects W.S.R. To Uterine Fibroids. And Endometrial Polyp - Gupta, Arun; Swati, Sipika; Dei, Laxmi Priya (International Research Journal of Ayurveda & Yoga, 2021)
Uterine Cavitary lesions (Adhimamsa/ Granthi/ Arbuda), known causes of female sub fertility and infertility. These lesions by virtue of their space occupying properties and pro-inflammatory nature may affect the successful implantation and provide a hostile environment for implantation & continuation of a pregnancy like a stone underneath a growing root. A 29 year old female nulligravida presented with failure to conceive for 2 years. Her investigations revealed multiple uterine fibroids and endometrial polyp. Kshetrikarana treatment helps in optimizing endometrial receptivity and creating a pro-conceptional environment. Therefore a composite treatment plan based on Dosha Dhatu vitiation, comprising of Samana chikitsa, Palasadi Yoga Basti and Garbhashaya lekhana was planned and implemented. Size of uterine fibroids reduced considerably after the treatment, endometrial polyp was removed by D&C. Patient conceived within four months of treatment and delivered a healthy full term female baby per vaginally without any ante-natal and post-natal complications albeit presence of the intra-mural fibroids.